2016
DOI: 10.17116/hirurgia2016411-14
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic interventions in diagnosis and treatment of Mirizzi syndrome

Abstract: It is shown that endoscopic transpapillary methods of diagnosis and treatment of Mirizzi syndrome provides adequate decompression and sanitation of the bile ducts in most cases and significantly reduces number of open surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…It has been reported that patients with Mirizzi syndrome have a high rate of conversion from LC to open cholecystectomy (1). Recently, ERCP has become the first-line method for the diagnosis of Mirizzi syndrome, with accuracy as high as 90% (6,7). ERCP is helpful for the Csendes classification, as the use of this technique can more clearly identify bile duct compression, as well as the presence of a bile duct gallbladder fistula or a gallbladder intestinal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with Mirizzi syndrome have a high rate of conversion from LC to open cholecystectomy (1). Recently, ERCP has become the first-line method for the diagnosis of Mirizzi syndrome, with accuracy as high as 90% (6,7). ERCP is helpful for the Csendes classification, as the use of this technique can more clearly identify bile duct compression, as well as the presence of a bile duct gallbladder fistula or a gallbladder intestinal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of periductal inflammation, MS can be mistakenly evaluated as gallbladder cancer, cholangiocarcinoma, or metastasis by ultrasonography or computed tomography [8]. The magnetic retrograde cholangiopancreatography procedure (MRCP) and endoscopic retrograde cholangiopancreatography (ERCP) can confirm the diagnosis in only half of the cases [9][10].…”
Section: Introductionmentioning
confidence: 99%